Bulwark to Battlefield: Religion in Quebec Literature - Shek, Ben-Z. (Journal of Canadian studies, 1983)
This article is an overview of the treatment of religious themes in Quebec literature in general and in the novel in particular. It first sets out the indissociable link between Catholicism and Quebec culture in its various manifestations. It then shows how aspects of the religious question were represented in the first hundred years of the novel form (1837-1937), almost exclusively in a traditional way. Note will be taken, however, of non-conformist works in that period which were harbingers of the counter-current. The latter emerged especially since 1938 and made the religious theme a battlefield, a prime target of contemporary writers.